The Megalomania of the Polish Noble Nation and the Demonstrative Speech of: Wojciech Dembołęcki’s “Wywód jedynowłasnego państwa świata” - Obremski, Krzysztof (Melusine. Old Literature and Culture, 2025)
The central claim of Wojciech Dembołęcki’s 1633 “Wywód jedynowłasnego państwa świata” (“On the Origin of the Only True State of the World”) comprises two parts: Adam and Eve spoke Polish, and the Kingdom of Poland was, according to Dembolęcki, “the only true state of the world”. This state surpassed and arguably eclipsed all other states. Dembołęcki, a Franciscan friar, combined his linguistic knowledge and unquestionable creativity in historical thought with etymological arguments in his work. The Horatian term “splendide mendax” can also be applied to Dembołęcki. His narrative of world history is admirable: it captivates the reader with its grand scope and the iron consistency expressed in the author’s imaginative concepts. It can be criticized for appealing to the vanity of the nobility. Regardless, this narrative about the essence of world history was highly rhetorical, rooted in the literary culture of the time. The work culminates in the poem „To Gryzosław”. This final text demonstrates the powerful connection between textual analysis and interpretation, known as feedback.